An Industrial systems study on Microwarehouse - de Celis, Excel Ann C.; Maluenda, Jo-ann D.; Parreño, Kristina E.; Ventura, Jonathan (College of Engineering, 2002)
"We are the preferred distributor of networking and mobile products. We are committed to the growth of our?partners through unparalleled support and services?people through continuous training and education." That has been the company mission statement of Microwavehouse ever since it started in 1995. The goal of the study is to analyze and evaluate the company from a total systems perspective in the light of the company mission. Strategic management allows an organization to be more proactive than reactive in shaping its own future. First the present system was document by looking into the external and internal environment of the system. Environmental scanning and Porter's Five was used to assess the external while the internal was audited by looking into the firm's resources, mission and goals. These elements define a set of conditions which define the company's strengths and weaknesses and the opportunities and threats which present themselves in the external environment. Strategies were formulated in a SWOT analysis and evaluated in a cost-impact matrix. The analysis and evaluation gave rise to five strategies for the company: differentiation, quantitative forecasting technique, intensive marketing campaign, proliferation of accessories and fast time-to-market. Major functional areas of forecasting, marketing and finance in order to trace the path toward the company's vision of Empowering Business Alliances thru Networking Technology. Strategic implementation and control for the aforementioned strategies were outlined. Time-phased implementation was indicated in Gantt charts.